The Right to Be Frivolous? An Intersectional Analysis of Gendered Harassment. Issue 1 (18th September 2019) - Li, Huey‐li
Abstract: In this essay, Huey‐li Li first undertakes a reexamination of the theoretical and practical merits of applying intersectionality to analyze how gender infiltrates and becomes entangled with other registers of nonsexual harassment. She further presents three vignettes of ambiguous nonsexual harassment in order to inquire into how the intersections among gender, disciplinary identity, disability, linguistic identity, and race/ethnicity shape divergent, unsettled, and ambiguous perceptions of harassment. Instead of seeking legal remedies for non‐monolithic gendered harassment, Li argues for systematic educational remedies that attend to the complex and complicated intersections between gender and the other registers of harassment in order to transform discriminatory and oppressive cultural practices.